2020
DOI: 10.1155/2020/4302608
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Lung Inflammation, but Not Lung Remodeling and Mechanics in a Model of Bleomycin-Induced Lung Fibrosis

Abstract: Introduction. Moderate aerobic exercise training accelerates the resolution of lung fibrosis in a model of bleomycin-induced pulmonary fibrosis. However, whether it can inhibit the development of lung fibrosis is unknown. Materials and Methods. C57Bl/6 mice were distributed into four groups: Control (Co), Exercise (Exe), Bleomycin (Bleo), and Bleomycin+Exercise (Bleo+Exe). A single bleomycin dose (1.5 UI/kg) was administered orotracheally and treadmill exercise started in the same day, enduring for 4 weeks, 5x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…The G protein-coupled receptor CysLT2, a LT receptor, is involved in inflammatory pain, and CysLT2 mRNA is positive for transient receptor potential vanilloid 1 (TRPV1), which releases CGRP and is highly colocalized with neurons [ 39 ]. Recent studies have also found that high levels of LTB4, a key endogenous molecule that induces the neutrophil inflammatory response, are associated with PF [ 40 ], and LTB4 biosynthesis blockade is now a potential strategy for the treatment of IPF and cystic PF [ 41 , 42 ]. Therefore, we speculate that upregulated lipid oxidation in Calca -KO animals might be an important contributor to the development of PF in these models.…”
Section: Discussionmentioning
confidence: 99%
“…The G protein-coupled receptor CysLT2, a LT receptor, is involved in inflammatory pain, and CysLT2 mRNA is positive for transient receptor potential vanilloid 1 (TRPV1), which releases CGRP and is highly colocalized with neurons [ 39 ]. Recent studies have also found that high levels of LTB4, a key endogenous molecule that induces the neutrophil inflammatory response, are associated with PF [ 40 ], and LTB4 biosynthesis blockade is now a potential strategy for the treatment of IPF and cystic PF [ 41 , 42 ]. Therefore, we speculate that upregulated lipid oxidation in Calca -KO animals might be an important contributor to the development of PF in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our animal experiment showed that CAV1 mRNA expression increased when treadmill exercise was performed in mice with pulmonary fibrosis. El-Mafarjeh et al ( El-Mafarjeh et al, 2020 ) showed that treadmill exercise improves pulmonary and systemic inflammation in bleomycin-induced pulmonary fibrosis models. This may be related to the fact in this study that treadmill increases CAV1, but the specific mechanisms need to be confirmed by further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…127 In terms of lung fibrosis and inflammation, 4 weeks of moderate intensity (60minutes, 5 times per week) treadmill running improved lung and systemic inflammation, but it did not inhibit bleomycin-induced lung fibrosis and remodeling in an animal study. 128 Others, however, have observed also accelerated resolution of lung fibrosis (reduced collagen fiber depositions) following 4-week exercise training in mice with bleomycin-induced lung fibrosis. 129…”
Section: Exercise and Bleomycin-induced Pulmonary Toxicitymentioning
confidence: 98%
“…Importantly, better results can be achieved when patients: (i) have more than 20 minutes of high intensity exercise in each session of aerobic training interventions, (ii) started to exercise prior to the treatment, and (iii) exercised for > 8 weeks in duration 127 . In terms of lung fibrosis and inflammation, 4 weeks of moderate intensity (60minutes, 5 times per week) treadmill running improved lung and systemic inflammation, but it did not inhibit bleomycin‐induced lung fibrosis and remodeling in an animal study 128 . Others, however, have observed also accelerated resolution of lung fibrosis (reduced collagen fiber depositions) following 4‐week exercise training in mice with bleomycin‐induced lung fibrosis 129 …”
Section: Exercise and Bleomycin‐induced Pulmonary Toxicitymentioning
confidence: 99%